Viperidae snake venom phospholipase A2. Biochemical targets in the human blood circulatory system. Review. Part 2 - L. V. Vasina; L. V. Galebskaya; М. А. Galkin; М. А. Solovyeva; Yu. V. Tarasova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2024)
In this review (Part 2), we describe the structural features and properties of the most studied Viperidae snake venom phospholipases A2 . Various effects of these enzymes on blood cells (erythrocytes, leukocytes and platelets), on blood coagulation and platelet aggregation are also analyzed in details. Possible areas and ways of application of these enzymes in fundamental and practical medicine are discussed.